Aproximación al psicodiagnóstico de Rorschach infantil - Rossel, Zoila (1987)
Our interest in investigating the children's Rorschach technique arose from the fact that there is an almost complete absence of information on the subject. On one hand, we refer to the discussions in which the different investigators participate. On the other hand, from our experience, we will present sorne opinions on technical aspects which will allow the clarification and union of criteria from which we can proposc new interpretative aspects, in a quantitative leve) and a qualitative one.